ANALISA PERENCANAAN DINDING PENAHAAN TANAH JL. BONTANG – SANGATTA STA 34+300 KIRI PROVINSI KALIMANTAN TIMUR - Rachmat Hidayat (KURVA MAHASISWA, 2016)
Retaining wall construction is a structure built to withstand ground sloped / slope where the soil stability can not be guaranteed by the land itself. Building retaining wall used to hold the lateral earth pressure caused by soil or soil urugan native unstable due to topographical conditions. The aim of this study was to plan for retaining wall in order to withstand the force Against Bolster, Slide and Stability (collapse). Calculation of earth pressure calculated stability against collapse of the soil bearing capacity. Results planning cantilever-type retaining walls using soil data on the laboratory test results to the Bontang location Sangatta in STA 34 + 300 left.